Development and Rasch Validation of a Teacher Profession Perception Scale for Education Students - Andini Shafa Akhmadi; Juntika Nurihsan; Idat Muqodas (Journal of Educational Sciences, 2026)
This study aimed to develop and validate a Teacher Profession Perception Scale for education students using the Rasch Model approach. The instrument was constructed based on the Factors Influencing Teaching Choice (FIT Choice) framework and measured four dimensions: teachers’ expert knowledge and job demands, social status of teachers, perception of teacher salary, and social discouragement. A quantitative instrument development design was employed involving expert judgment, readability testing, and field testing with 75 respondents from teacher education related programs. Initially consisting of 33 items, the instrument was reduced to 25 items following screening and refinement procedures. Rasch analysis yielded an item reliability of 0.99, an item separation index of 8.16, a person reliability of 0.55, and a Cronbach's alpha of 0.59. The rating scale analysis confirmed that the seven point response categories functioned appropriately, while Differential Item Functioning analysis indicated that most items were free from substantial demographic bias. Overall, the findings suggest that the Teacher Profession Perception Scale possesses acceptable psychometric properties and can be used as a valid and reliable instrument for measuring education students’ perceptions toward the teaching profession.